Asymmetric ceramic hollow fiber nanofiltration membrane and preparation method thereof
By adopting the structural design of asymmetric ceramic hollow fiber nanofiltration membrane, the problem that existing ceramic membranes are difficult to reduce mass transfer resistance while increasing the loading density and specific surface area is solved, achieving a more efficient separation process and cost-reducing effect .
Patent Information
- Application Number
- CN202411476712.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-25
AI Technical Summary
While increasing the loading density and specific surface area, existing ceramic membranes are difficult to effectively reduce mass transfer resistance during separation, and the modification procedures of tubular membranes are cumbersome, which increases costs and resistance.
The structural design of asymmetric ceramic hollow fiber nanofiltration membrane is adopted, and the ceramic hollow fiber membrane matrix, γ-mesoporous intermediate layer and micropore separation layer are successively formed from the inside to the outside. The γ-mesoporous intermediate layer and the micropore separation layer are formed through a specific preparation method. Microporous separation layer reduces mass transfer resistance.
It is achieved while providing a larger filling density and specific surface area, while reducing mass transfer resistance during separation, increasing water flux and reducing preparation costs.
Smart Images

Figure CN119499891A_ABST
Abstract
Description
Technical Field The invention belongs to the field of liquid separation, and in particular relates to the structural design of an asymmetric ceramic hollow fiber nanofiltration membrane using a sol-gel method. Background Art Compared with traditional separation technologies such as adsorption, distillation, extraction, etc., membrane separation technology is widely used in seawater desalination, petrochemical, food engineering, biomedicine, wastewater treatment and other fields due to its low consumption, high efficiency and environmental friendliness. Compared with polymer membranes, ceramic membranes have significant advantages in durability, hydrothermal stability, chemical stability, mechanical strength, antibacterial, backwashing ability, etc. Ceramic membranes are particularly suitable for areas with high temperature, high pressure, organic solvents, harsh feed environment and serious pollution. In these areas, traditional polymer membranes cannot be used or are inefficient due to serious fouling and material instability. However, the widespread application of ceramic membranes in the market still faces challenges, especially in reducing investment and manufacturing costs, increasing packing density and reducing mass transfer resistance. In the prior art, there are methods to reduce the mass transfer resistance in the separation process by controlling the thickness of the separation layer and chemically modifying the sol-gel, but the low packing density of the tubular membrane and the extra investment cost and mass transfer resistance caused by the cumbersome modification procedures are still problems to be solved. It is desirable to obtain a ceramic hollow fiber membrane that can provide a larger packing density and specific surface area while reducing the mass transfer resistance in the separation process. Summary of the invention In order to solve the problems existing in the prior art, the present inventors conducted in-depth research and found that the asymmetric ceramic hollow fiber nanofiltration membrane provided by the present invention can solve at least one technical problem existing in the prior art. In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0001] An asymmetric ceramic hollow fiber nanofiltration membrane comprises, from inside to outside, a ceramic hollow fiber membrane matrix, a γ-mesoporous intermediate layer, and a microporous separation layer. The ceramic hollow fiber membrane substrate has a tube diameter of 1.5 to 2 mm, a thickness of 300 to 400 μm, and an average pore size of 150 to 300 nm. The thickness of the γ-mesoporous intermediate layer is 1 to 5 μm, and the average pore diameter is 5 to 10 nm. The thickness of the microporous separation layer is 100-500 nm, and the average pore diameter is 1-1.6 nm.
[0002] A method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane, wherein the asymmetric ceramic hollow fiber nanofiltration membrane is the asymmetric ceramic hollow fiber nanofiltration membrane described in [1]. The preparation method comprises the steps of: coating a ceramic hollow fiber membrane substrate with boehmite sol and then sintering to form a γ-mesoporous intermediate layer, and then coating a SiO2-ZrO2 sol and then sintering to form a microporous separation layer.
[0003] According to the method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane described in [2], the ceramic hollow fiber membrane substrate is formed by the following steps: Slurry preparation steps: adding a polymer and a binder into an organic solvent to fully dissolve them, and then adding ceramic powder and mixing them evenly to form a ceramic slurry; Precursor preparation step: vacuum degassing the ceramic slurry, using deionized water as an internal coagulation liquid, extruding the ceramic slurry into deionized water through a single-layer spinneret, curing, and then naturally drying to obtain a ceramic hollow fiber precursor; Sintering step: sintering the ceramic hollow fiber precursor at 500-800° C. for 1-3 hours to remove organic matter in the precursor, and then sintering at 1400-1600° C. for 4-10 hours to obtain a ceramic hollow fiber membrane matrix.
[0004] According to the method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane described in [2], the process of dip-coating boehmite sol on the ceramic hollow fiber membrane substrate and then sintering to form a γ-mesoporous intermediate layer comprises the following steps: The boehmite sol preparation steps are as follows: dissolving a metal precursor in water and stirring to form an emulsion, adding a peptizing agent, and continuing to reflux and age for 10 to 20 hours to obtain a stable boehmite sol, wherein the mass ratio of the metal precursor, the peptizing agent and water is 1: (0.4 to 1): (5 to 13), and then mixing with a 3 to 10 wt% aqueous solution of polyvinyl alcohol to obtain the boehmite sol. The step of forming the γ-mesoporous intermediate layer is as follows: immersing the ceramic hollow fiber membrane substrate in the boehmite sol, and then dip-coating the boehmite sol on the ceramic hollow fiber membrane substrate by an immersion and pulling method, and then sintering at 600 to 900° C. for 2 to 4 hours, thereby forming the γ-mesoporous intermediate layer on the ceramic hollow fiber membrane substrate.
[0005] According to the method for preparing the asymmetric ceramic hollow fiber nanofiltration membrane described in [2], the step of impregnating SiO2-ZrO2 sol and then sintering to form a microporous separation layer comprises the following steps: Preparation steps of SiO2-ZrO2 sol: TEOS and ZrBT are added to ethanol solvent in sequence at intervals of 3 hours and stirred, and then water and hydrochloric acid are added and refluxed to form SiO2-ZrO2 sol; The microporous separation layer forming step: after forming the γ-mesoporous intermediate layer, the formed γ-mesoporous intermediate layer is dip-coated in the SiO2-ZrO2 sol by dipping and pulling for more than one time, and after natural drying, it is sintered at 500-550° C. for 0.5-1 hour, and the heating rate is 0.5-1° C. / min. The microporous separation layer forming step is repeated one or more times.
[0006] According to the method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane described in [3], in the slurry preparation step for forming the ceramic hollow fiber membrane matrix, the polymer is at least one selected from polysulfone or polyethersulfone; the organic solvent is at least one selected from N-methylpyrrolidone and dimethyl sulfoxide, the binder is polyvinylpyrrolidone, and the ceramic powder is α-Al2O3 with a particle size of 200 to 400 nm.
[0007] According to the method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane described in [4], wherein in the boehmite sol preparation step, the metal precursor is at least one selected from aluminum sec-butoxide (ASB) and aluminum isopropoxide; the peptizing agent is 0.1 to 1 mol / L nitric acid or acetic acid, In the step of forming the γ-mesoporous intermediate layer, the pulling speed is 100-200 mm / min, the dipping time is 10-60 s, the dipping times are 1-3 times, sintering is performed at 600-900° C. for 2-4 h, and the heating rate is 1-3° C. / min.
[0008] According to the preparation method of the asymmetric ceramic hollow fiber nanofiltration membrane described in [5], in the step of forming the microporous separation layer, the pulling speed is 100-200 mm / min, the dipping time is 10-60 s, the number of dipping times is 1-3 times, and the sintering is performed at 500-550°C for 0.5-1 hour, and the heating rate is 0.5-1°C / min. Effects of the Invention The asymmetric ceramic hollow fiber nanofiltration membrane of the present invention can reduce the mass transfer resistance in the separation process while providing a larger packing density and specific surface area. The method for preparing the asymmetric ceramic hollow fiber nanofiltration membrane of the present invention can prepare an asymmetric ceramic hollow fiber nanofiltration membrane which can provide a larger packing density and specific surface area while reducing the mass transfer resistance in the separation process. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 A schematic diagram of an asymmetric ceramic hollow fiber nanofiltration membrane is shown according to one embodiment. Figure 2 The scanning electron microscope image ( Figure 2 ) and a scanning electron microscope image of the surface of the substrate of the hollow fiber membrane ( Figure 2 (right image). Figure 3 The scanning electron microscope image of the cross section of the γ-mesoporous intermediate layer of the asymmetric ceramic hollow fiber nanofiltration membrane prepared in Example 1 is shown ( Figure 3 Left image) and the SEM image of the surface of the γ-mesoporous intermediate layer of the hollow fiber membrane ( Figure 3 (right image). Figure 4 The scanning electron microscope image ( Figure 4 Left image), enlarged image of the box part ( Figure 4 ) and a scanning electron microscope image of the surface of the microporous separation layer of the hollow fiber membrane ( Figure 4 (right image). Reference numerals 1: Ceramic hollow fiber membrane matrix 2: γ-mesoporous intermediate layer 3: Microporous separation layer DETAILED DESCRIPTION In order to better understand the present invention, the present invention is further described in detail below in conjunction with the embodiments, but the scope of protection claimed in the present invention is not limited to the scope represented by the embodiments. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present disclosure. The asymmetric ceramic hollow fiber nanofiltration membrane of the present invention comprises, from the inside to the outside, a ceramic hollow fiber membrane matrix, a γ-mesoporous intermediate layer, and a microporous separation layer. Figure 1 A schematic diagram of an asymmetric ceramic hollow fiber nanofiltration membrane is shown according to one embodiment. Figure 1 The asymmetric ceramic hollow fiber nanofiltration membrane shown has a ceramic hollow fiber membrane substrate 1, a γ-mesoporous intermediate layer 2 and a microporous separation layer 3 from the inside to the outside. The aforementioned ceramic hollow fiber membrane substrate has a tube diameter of 1.5 to 2 mm, a thickness of 300 to 400 μm, and an average pore size of 150 to 300 nm. The thickness of the aforementioned γ-mesoporous intermediate layer is 1 to 5 μm, and the average pore diameter is 5 to 10 nm. The thickness of the aforementioned microporous separation layer is 100 to 500 nm, and the average pore diameter is 1 to 1.6 nm. When the conventional ceramic nanofiltration membrane uses a commercial membrane with a pore size range of about 1 to 10 microns as a matrix, in order to reduce the pore size to tens of nanometers, it is necessary to modify the surface of the commercial membrane 5 to 10 times by means of a ceramic particle coating to achieve the pore size and smooth surface required for preparing the microporous separation layer on the surface. The asymmetric ceramic hollow fiber nanofiltration membrane of the present application directly modifies the γ-mesoporous intermediate layer by using a ceramic hollow fiber membrane matrix with an average pore size of 150 to 300 nm, and does not require the aforementioned 5 to 10 modification layers, so the mass transfer resistance is reduced. In addition, by using a ceramic hollow fiber membrane matrix with a small diameter of 1.5 to 2 mm in the asymmetric ceramic hollow fiber nanofiltration membrane, the packing density can be increased relative to the matrix with a diameter of about 10 mm used in the conventional ceramic nanofiltration membrane. The aforementioned asymmetric ceramic hollow fiber nanofiltration membrane can be prepared by, for example, the following preparation method, namely, a preparation method comprising dip-coating boehmite sol on the ceramic hollow fiber membrane substrate and then sintering to form a γ-mesoporous intermediate layer, and then dip-coating SiO2-ZrO2 sol and then sintering to form a microporous separation layer. The aforementioned ceramic hollow fiber membrane substrate is formed, for example, by the following steps: Slurry preparation steps: adding a polymer and a binder into an organic solvent to fully dissolve them, and then adding ceramic powder and mixing them evenly to form a ceramic slurry; Precursor preparation step: vacuum degassing the aforementioned ceramic slurry, using deionized water as an internal coagulation liquid, extruding the aforementioned ceramic slurry into deionized water through a single-layer spinneret, curing, and then naturally drying to obtain a ceramic hollow fiber precursor; Sintering step: sinter the aforementioned ceramic hollow fiber precursor at 500-800° C. for 1-3 hours to remove organic matter in the aforementioned precursor, and then sinter at 1400-1600° C. for 4-10 hours to obtain a ceramic hollow fiber membrane substrate. The ceramic hollow fiber membrane matrix formed by the above steps utilizes the phase inversion principle. The obtained hollow fiber membrane matrix has a relatively dense epidermis, which makes it easier to achieve the pore size and smooth surface required by the microporous separation layer on the surface. Compared with the traditional layer-by-layer particle coating modification process of tubular membranes, the additional mass transfer resistance caused by the cumbersome modification procedures is reduced. In addition, the hollow fiber membrane matrix obtained in this way has a greater packing density than the tubular membrane. In the method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane in one embodiment, the process of dip-coating boehmite sol on the ceramic hollow fiber membrane substrate and then sintering to form a γ-mesoporous intermediate layer comprises the following steps: The boehmite sol preparation steps are as follows: after dissolving the metal precursor in water and stirring to form an emulsion, a peptizing agent is added, and reflux aging is continued for 10 to 20 hours to obtain a stable boehmite sol, wherein the mass ratio of the aforementioned metal precursor, the peptizing agent and water is 1: (0.4 to 1): (5 to 13), and then mixed with a 3 to 10 wt% aqueous solution of polyvinyl alcohol to obtain the boehmite sol. The steps of forming the γ-mesoporous intermediate layer are as follows: immersing the ceramic hollow fiber membrane substrate in the aforementioned boehmite sol, and then dip-coating the aforementioned boehmite sol on the aforementioned ceramic hollow fiber membrane substrate by an immersion and pulling method, and then sintering at 600 to 900°C for 2 to 4 hours, thereby forming the aforementioned γ-mesoporous intermediate layer on the aforementioned ceramic hollow fiber membrane substrate. In the method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane in one embodiment, the process of sintering to form a microporous separation layer after dipping SiO2-ZrO2 sol comprises the following steps: Preparation steps of SiO2-ZrO2 sol: TEOS and ZrBT are added to ethanol solvent in sequence at intervals of 3 hours and stirred, and then water and hydrochloric acid are added and refluxed to form SiO2-ZrO2 sol; The microporous separation layer formation step is as follows: the SiO2-ZrO2 sol is dip-coated for more than one time by dipping and pulling, and then naturally dried and sintered at 500-550°C for 0.5-1 hour at a heating rate of 0.5-1°C / min. The aforementioned microporous separation layer forming step may be repeated one or more times. In the preparation method of an asymmetric ceramic hollow fiber nanofiltration membrane according to one embodiment, in the aforementioned slurry preparation step for forming the ceramic hollow fiber membrane matrix, the aforementioned polymer is at least one selected from polysulfone or polyethersulfone; the aforementioned organic solvent is at least one selected from N-methylpyrrolidone and dimethyl sulfoxide, the aforementioned binder is polyvinylpyrrolidone, and the aforementioned ceramic powder is α-Al2O3 with a particle size of 200 to 400 nm. In the method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane according to one embodiment, in the boehmite sol preparation step, the metal precursor is at least one selected from aluminum sec-butoxide (ASB) and aluminum isopropoxide; the peptizing agent is 0.1 to 1 mol / L nitric acid or acetic acid, In the aforementioned γ-mesoporous intermediate layer formation step, the aforementioned pulling speed is 100-200 mm / min, the aforementioned dipping time is 10-60 s, the number of dipping times is 1-3 times, sintering is performed at 600-900°C for 2-4h, and the heating rate is 1-3°C / min. In one embodiment of a method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane, in the aforementioned microporous separation layer formation step, the aforementioned pulling speed is 100-200 mm / min, the aforementioned dipping time is 10-60 s, the number of dipping times is 1-3 times, and it is sintered at 500-550°C for 0.5-1 hour, and the heating rate is 0.5-1°C / min. Example Pure water permeability test: seal one end of the membrane, use a pressure pump to transfer water from the outside of the membrane to the inside of the membrane, and collect the permeate at the inner outlet of the membrane. The water permeability is the volume of water per unit time per unit membrane area per unit pressure. Embodiment 1: First, polyethersulfone (Aladdin, Shanghai Tengzhun Biotechnology Co., Ltd.) and polyvinylpyrrolidone (Aladdin, Shanghai Tengzhun Biotechnology Co., Ltd.) as a binder are added to N-methylpyrrolidone (Aladdin, Shanghai Tengzhun Biotechnology Co., Ltd.) in turn and stirred vigorously for 5 hours to fully dissolve it. Then, α-Al2O3 ceramic powder (Aladdin, Shanghai Tengzhun Biotechnology Co., Ltd.) is added and stirred vigorously for 48 hours to uniformly disperse it into the polymer solution to form a ceramic slurry; the weight proportion of each component in the ceramic powder slurry is: polyethersulfone: N-methylpyrrolidone: 400nm ceramic powder: 200nm ceramic powder = 8.4wt%: 41.1wt%: 41.1wt%: 8.4wt%, and the polyvinylpyrrolidone binder accounts for 1wt% of the total slurry. The ceramic slurry was vacuum degassed for 2 hours to remove bubbles in the slurry; after degassing, the ceramic slurry was transferred to a stainless steel syringe, and deionized water was used as the core liquid. The ceramic slurry was extruded into a deionized water external coagulation bath through a single-layer spinneret for curing for 24 hours, wherein the flow rates of the core liquid and the ceramic slurry were 12 mL / min and 6 mL / min, respectively, to obtain a ceramic hollow fiber precursor. After the cured ceramic hollow fiber precursor was naturally dried for 24 hours, it was placed in a high-temperature box furnace and sintered at 800°C for 1 hour to remove the organic matter therein, and then sintered at 1500°C for 5 hours, with the heating rate and cooling rate both being 3°C / min, and finally the matrix of the asymmetric ceramic hollow fiber nanofiltration membrane was obtained. The matrix of the asymmetric ceramic hollow fiber nanofiltration membrane was photographed using a scanning electron microscope, and the thickness and diameter of the matrix were measured. Figure 2 The SEM image of the cross section of the prepared substrate is shown ( Figure 2 The left image) and the SEM image of the surface of the substrate ( Figure 2 The diameter of the substrate was measured to be about 1.8 mm, the thickness was about 300 μm, the mechanical strength was about 150 MPa (three-point bending technique, electronic universal testing machine CMT-05), and the average pore size was about 150 nm (bubble point method, capillary flow pore size analyzer). 24.63g of aluminum sec-butoxide (Aladdin, Shanghai Tengzhun Biological and Technology Co., Ltd.) was added to 90°C deionized water and stirred for 1 hour to form a white emulsion, and then 1M nitric acid (25mL) was added and stirred for 1 hour to form a blue transparent boehmite sol, and then refluxed and aged for 15 hours to form a stable boehmite sol. 5wt% polyvinyl alcohol aqueous solution (Aladdin, Shanghai Tengzhun Biological and Technology Co., Ltd.) was added to the aforementioned boehmite sol to prevent cracks from forming on the coating surface during the sintering process described later. Then the cleaned ceramic hollow fiber membrane substrate was dip-coated in the aforementioned boehmite sol, wherein the pulling speed was 200mm / min, the dipping time was 60s, and the number of dippings was 2 times. After dipping, it was dried in a clean shed for 24 hours and then placed in a box-type muffle furnace and sintered at 600°C for 2 hours, with a heating rate of 1°C / min, and a γ-mesoporous intermediate layer was formed on the substrate surface of the asymmetric ceramic hollow fiber nanofiltration membrane prepared above. The γ-mesoporous interlayer was photographed using a scanning electron microscope. Figure 3 The SEM image of the cross section of the prepared γ-mesoporous interlayer ( Figure 3 The left image) and the SEM image of the surface of the γ-mesoporous intermediate layer ( Figure 3 The thickness of the obtained γ-mesoporous interlayer is 2.5 μm and the average pore size is about 5.7 nm. 3.52 g TEOS (Aladdin, Shanghai Tengzhun Biological and Technology Co., Ltd.) and 6.48 g ZrBT (Aladdin, Shanghai Tengzhun Biotechnology Co., Ltd.) After adding an appropriate amount of ethanol solvent at intervals of 3 hours and stirring for 12 hours, a large amount of water and hydrochloric acid were added and refluxed for 8 hours to form a stable SiO2-ZrO2 sol, and the total volume of the solution was maintained at 500mL. The γ-mesoporous intermediate obtained above was dip-coated in the SiO2-ZrO2 sol, wherein the pulling speed was 200mm / min, the dipping time was 60s, and the number of dipping times was 3 times. After dipping, it was dried in a clean shed for 24 hours and then placed in a box-type muffle furnace and sintered at 500°C for 30 minutes, with a heating rate of 0.5°C / min to obtain an asymmetric ceramic hollow fiber nanofiltration membrane. The microporous separation layer was photographed using a scanning electron microscope. Figure 4 The scanning electron microscope image of the cross section of the obtained microporous separation layer is shown ( Figure 4 Left image), its partial enlarged image ( Figure 4 The middle image of the microporous separation layer) and the scanning electron microscope image of the surface of the microporous separation layer ( Figure 4 The thickness of the microporous separation layer is 200 nm, the average pore size is about 1.5 nm, and the packing density is 918 m 2 / m 3 . The asymmetric ceramic hollow fiber nanofiltration membrane prepared above was subjected to a pure water permeability test, and its water flux was 9.6 (LMH / bar). Example 2 Except that the sintering temperature of the γ-mesoporous intermediate layer was changed from 600°C to 750°C, the rest was carried out in the same manner as in Example 1 to prepare an asymmetric ceramic hollow fiber nanofiltration membrane. The cross-sections of each layer were photographed using a scanning electron microscope. The thickness of the γ-mesoporous intermediate layer in the obtained asymmetric ceramic hollow fiber nanofiltration membrane was 2.5 μm, the average pore size was about 6.7 nm, the thickness of the microporous separation layer was 200 nm, the average pore size was about 1.5 nm, and the packing density was 918 m 2 / m 3 . The obtained asymmetric ceramic hollow fiber nanofiltration membrane was subjected to a pure water permeability test, and its water flux was 12.53 (LMH / bar). Example 3 Except that the sintering temperature of the γ-mesoporous intermediate layer was changed from 600°C to 900°C, the rest was carried out in the same manner as in Example 1 to prepare an asymmetric ceramic hollow fiber nanofiltration membrane. The cross-sections of each layer were photographed using a scanning electron microscope. The thickness of the γ-mesoporous intermediate layer in the obtained asymmetric ceramic hollow fiber nanofiltration membrane was 2.5 μm, the average pore size was about 9.9 nm, the thickness of the microporous separation layer was 200 nm, the average pore size was about 1.5 nm, and the packing density was 918 m 2 / m 3 . The obtained asymmetric ceramic hollow fiber nanofiltration membrane was subjected to a pure water permeability test, and its water flux was 22.44 (LMH / bar). Comparative Example 1 The substrate is a tubular ceramic membrane with a pore size of about 2μm and a tube diameter of about 12mm. The preparation method of SiO2-ZrO2 sol is the same as that of Example 1. 10wt% of ceramic powder with an average particle size of about 2μm is dispersed in the above-mentioned SiO2-ZrO2 sol and stirred for 6 hours to form a large particle suspension, and then the cleaned tubular ceramic membrane substrate is placed in the aforementioned large particle suspension for dip coating, wherein the pulling speed is 200mm / min, the dipping time is 60s, and the number of dipping times is 2 times. After dipping, dry it in a clean shed for 24 hours, then put it into a box-type muffle furnace and sinter it at 550°C for 30 minutes, and the heating rate is 1°C / min. This process is repeated 5 times. 10wt% ceramic powder with an average particle size of about 0.2μm is dispersed in SiO2-ZrO2 sol and stirred for 6 hours to form a small particle suspension. Then the tubular ceramic membrane substrate modified by the large particle suspension is dip-coated in the aforementioned small particle suspension, wherein the pulling speed is 200mm / min, the dipping time is 60s, and the number of dipping times is 2 times. After dipping, it is dried in a clean shed for 24 hours and then placed in a box-type muffle furnace and sintered at 550℃ for 30 minutes, with a heating rate of 1℃ / min. This process is repeated 4 times to form a mesoporous intermediate layer. The thickness of the obtained particle mesoporous intermediate layer is 5μm, and the average pore size is about 5-10nm. The above-obtained particle mesoporous intermediate was dip-coated in SiO2-ZrO2 sol, wherein the pulling speed was 200 mm / min, the dipping time was 60 s, and the dipping times were 3 times. After dipping, it was dried in a clean room for 24 hours and then placed in a box-type muffle furnace and sintered at 500°C for 30 minutes at a heating rate of 0.5°C / min to form a microporous separation layer. The obtained microporous separation layer had a thickness of 200 nm, an average pore size of about 1.5 nm, and a packing density of 330 m 2 / m 3 . The obtained hollow fiber membrane was subjected to a pure water permeability test, and the water flux thereof was 0.72 (LMH / bar). The above embodiments and comparative examples illustrate that the asymmetric ceramic hollow fiber nanofiltration membrane of the present invention reduces the mass transfer resistance in the separation process while providing a larger packing density and specific surface area, and the water flux is increased by an order of magnitude compared with the traditional tubular nanofiltration membrane. Obviously, the above embodiments of the present disclosure are merely examples for clearly illustrating the present disclosure, and are not limitations on the implementation methods of the present disclosure. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present disclosure are still within the protection scope of the present disclosure.
Claims
1. An asymmetric ceramic hollow fiber nanofiltration membrane, characterized in that: It has a ceramic hollow fiber membrane matrix, a γ-mesoporous intermediate layer, and a microporous separation layer from the inside to the outside. The ceramic hollow fiber membrane substrate has a tube diameter of 1.5 to 2 mm, a thickness of 300 to 400 μm, and an average pore size of 150 to 300 nm. The thickness of the γ-mesoporous intermediate layer is 1 to 5 μm, and the average pore diameter is 5 to 10 nm. The thickness of the microporous separation layer is 100-500 nm, and the average pore diameter is 1-1.6 nm.
2. A method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane, wherein the asymmetric ceramic hollow fiber nanofiltration membrane is the asymmetric ceramic hollow fiber nanofiltration membrane according to claim 1, The preparation method comprises the steps of: coating a ceramic hollow fiber membrane substrate with boehmite sol and then sintering to form a γ-mesoporous intermediate layer, and then coating a SiO2-ZrO2 sol and then sintering to form a microporous separation layer.
3. The method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane according to claim 2, wherein: The ceramic hollow fiber membrane substrate is formed by the following steps: Slurry preparation steps: adding a polymer and a binder into an organic solvent to fully dissolve them, and then adding ceramic powder and mixing them evenly to form a ceramic slurry; Precursor preparation step: vacuum degassing the ceramic slurry, using deionized water as an internal coagulation liquid, extruding the ceramic slurry into deionized water through a single-layer spinneret, curing, and then naturally drying to obtain a ceramic hollow fiber precursor; Sintering step: sintering the ceramic hollow fiber precursor at 500-800° C. for 1-3 hours to remove organic matter in the precursor, and then sintering at 1400-1600° C. for 4-10 hours to obtain a ceramic hollow fiber membrane matrix.
4. The method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane according to claim 2, wherein: The process of dip-coating boehmite sol on the ceramic hollow fiber membrane substrate and then sintering to form a γ-mesoporous intermediate layer comprises the following steps: The boehmite sol preparation step comprises: dissolving a metal precursor in water and stirring to form an emulsion, adding a peptizing agent, and continuing to reflux and age for 10 to 20 hours to obtain a stable boehmite sol, wherein the mass ratio of the metal precursor, the peptizing agent and water is 1:0.4 to 1:5 to 13, and then mixing with a 3 to 10 wt% aqueous solution of polyvinyl alcohol to obtain the boehmite sol; The step of forming the γ-mesoporous intermediate layer is as follows: immersing the ceramic hollow fiber membrane substrate in the boehmite sol, and then dip-coating the boehmite sol on the ceramic hollow fiber membrane substrate by an immersion and pulling method, and then sintering at 600 to 900° C. for 2 to 4 hours, thereby forming the γ-mesoporous intermediate layer on the ceramic hollow fiber membrane substrate.
5. The method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane according to claim 2, wherein: The step of sintering the SiO2-ZrO2 sol to form a microporous separation layer comprises the following steps: Preparation steps of SiO2-ZrO2 sol: TEOS and ZrBT are added to ethanol solvent in sequence at intervals of 3 hours and stirred, and then water and hydrochloric acid are added and refluxed to form SiO2-ZrO2 sol; The microporous separation layer forming step: after forming the γ-mesoporous intermediate layer, the formed γ-mesoporous intermediate layer is dip-coated in the SiO2-ZrO2 sol by dipping and pulling for more than one time, and after natural drying, it is sintered at 500-550° C. for 0.5-1 hour, and the heating rate is 0.5-1° C. / min. The microporous separation layer forming step is repeated one or more times.
6. The method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane according to claim 3, wherein: In the slurry preparation step for forming a ceramic hollow fiber membrane matrix, the polymer is at least one selected from polysulfone or polyethersulfone; the organic solvent is at least one selected from N-methylpyrrolidone and dimethyl sulfoxide, the binder is polyvinylpyrrolidone, and the ceramic powder is α-Al2O3 with a particle size of 200 to 400 nm.
7. The method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane according to claim 4, wherein: In the boehmite sol preparation step, the metal precursor is at least one selected from aluminum sec-butoxide and aluminum isopropoxide; the peptizing agent is 0.1-1 mol / L nitric acid or acetic acid, In the step of forming the γ-mesoporous intermediate layer, the pulling speed is 100-200 mm / min, the dipping time is 10-60 s, the dipping times are 1-3 times, sintering is performed at 600-900° C. for 2-4 h, and the heating rate is 1-3° C. / min.
8. The method for preparing an asymmetric ceramic hollow fiber nanofiltration membrane according to claim 5, wherein: In the microporous separation layer forming step, the pulling speed is 100-200 mm / min, the dipping time is 10-60 s, the number of dippings is 1-3 times, sintering is performed at 500-550°C for 0.5-1 hour, and the heating rate is 0.5-1°C / min.
Citation Information
Cited By
Porous ceramic tube and preparation method thereof
CN121449445A
Porous ceramic tube and method for producing the same
CN121449445B